2013
DOI: 10.1073/pnas.1301480110
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Dominant suppression of inflammation by glycan-hydrolyzed IgG

Abstract: The authors wish to note the following: "Using studies of IgG hydrolyzed by the streptococcal glycan hydrolyzing enzyme EndoS, we found that treatment of mice with hydrolyzed IgG blocked antibody mediated arthritis. As an explanation for this observation, we suggested that EndoS-hydrolyzed IgG per se dominantly blocks local immune complex formation."With new data from our own follow up experiments, we have now found that this conclusion was incorrect."Our new data shows that injection of EndoS is much more pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Many epidemiological studies and experimental observations have demonstrated that changes in IgG Fc glycosylation induce pro-inflammatory or anti-inflammatory actions of Igs, [ 10 , 20 , 39 , 40 ] indicating that IgG Fc glycosylation plays an important role in the process of aging. [ 29 , 41 ] The reduction of terminal galactose residues was suggested as a mechanism to enhance the pro-inflammatory activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies and experimental observations have demonstrated that changes in IgG Fc glycosylation induce pro-inflammatory or anti-inflammatory actions of Igs, [ 10 , 20 , 39 , 40 ] indicating that IgG Fc glycosylation plays an important role in the process of aging. [ 29 , 41 ] The reduction of terminal galactose residues was suggested as a mechanism to enhance the pro-inflammatory activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…EndoS has been successful in in vivo studies for the treatment of model systems of rheumatoid arthritis, experimental glomerulonephritis, and systemic lupus erythematosus (11, 1517). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GlycoDelete technology favors production of antibodies when the case is neutralization of antigen rather than additional effector function. Likewise, the reduced N-glycanprotocol is important in the biopharmaceutical industry, and the benefits of short N-glycans have also been reported (160)(161)(162).…”
Section: Glycodelete Technologymentioning
confidence: 99%